An integrated method for taxonomic identif ication of microorganisms - Yu. E. Uvarova; A. V. Bryanskaya; A. S. Rozanov; V. N. Shlyakhtun; E. A. Demidov; K. V. Starostin; T. N. Goryachkovskaya; S. V. Shekhovtsov; N. M. Slynko; S. E. Peltek (Вавиловский журнал генетики и селекции)
For accurate species-level identification of microorganisms, researchers today increasingly use a combination of standard microbiological cultivation and visual observation methods with molecular biological and genetic techniques that help distinguish between species and strains of microorganisms at the level of DNA or RNA molecules. The aim of this work was to identify microorganisms from the ICG SB RAS Collection using an integrated approach that involves a combination of various phenotypic and genotypic characteristics. Key molecular-genetic and phenotypic characteristics were determined for 93 microbial strains from the ICG SB RAS Collection. The strains were characterized by means of morphological, physiological, moleculargenetic, and mass-spectrometric parameters. Specific features of the growth of the strains on different media were determined, and cell morphology was evaluated. The strains were tested for the ability to utilize various substrates. The strains studied were found to significantly differ in their biochemical characteristics. Physiological characteristics of the strains from the collection were identified too, e. g., the relationship with oxygen, type of nutrition, suitable temperature and pH ranges, and NaCl tolerance. In this work, the microorganisms analyzed were combined into separate groups based on the similarities of their phenotypic characteristics. This categorization, after further refinement and expansion of the spectrum of taxa and their metabolic maps, may serve as the basis for the creation of an “artificial” classification that can be used as a key for simplified and quicker identification and recognition of microorganisms within both the ICG SB RAS Collection and other collections.